233k views
25 votes
I need help doing this... I’m totally lost

I need help doing this... I’m totally lost-example-1
User EdCornejo
by
4.5k points

1 Answer

3 votes

Answer:


-(a+1(3)/(4)b)

Explanation:

Perimeter of a polygon = Sum of the measures of all sides of the polygon

For the given trapezoid,

Perimeter =
1(1)/(2)a+1(1)/(2)b+1(1)/(2)a+2(3)/(4)b

By combining similar terms,

Perimeter =
(1(1)/(2)+1(1)/(2))a+(1(1)/(2)+2(3)/(4))b

=
(1+(1)/(2)+1+(1)/(2))a+(1+(1)/(2)+2+(3)/(4))b

= (2 + 1)a +
(3+(1)/(2)+(3)/(4))b

= 3a +
(3+(2)/(4)+ (3)/(4))b

= 3a +
(3+(5)/(4))b

= 3a +
(3+1+(1)/(4))b

= 3a +
4(1)/(4)b

For rectangle,

Perimeter = 2(Length + Width)

= 2(2a + 3b)

Difference between the perimeter of trapezoid and rectangle,

= (3a +
4(1)/(4)b) - 2(2a + 3b)

= (3a - 4a) + (
4(1)/(4)b - 6b)

= -a +
(4+(1)/(4)-6)b

= -a +
((1)/(4)-2)b

= -a +
((1)/(4)-(8)/(4))b

= -a -
(7)/(4)b

=
-(a+1(3)/(4)b)

User JuanBonnett
by
4.5k points